Land cover mapping of Bengaluru's urban and surrounding area with Spatiotemporal open-source remote sensing data - Grison, Sylvain; Siddaganga, Rajath; Singh, Renu; Hegde, Shrihari; Brockmann, Axel; Krishnan, Smitha; Guo, Wei (MYU K.K., 2023)
The rapid urbanization observed in Asian tropics has resulted in extensive landscape transformations, giving rise to novel challenges such as conflicts of interest among citizens and threats to biodiversity. To facilitate informed urban management policies, there is a pressing need for contemporary land use and cover maps that provide precise insights into the evolving landscape. In this paper, we present the city of Bengaluru, India (covering an area of 365,879 ha) as a case study. We introduce an open-source-driven pipeline method capable of generating an updated 11-class land cover map at a high resolution of 10 m, achieving a global F1 score of 0.82. Notably, our proposed pipeline represents a pioneering solution that effectively addresses the persistent issue of cloud cover caused by monsoons, enhancing the utility of such maps for urban management, and planning in rapidly evolving regions.